APLIKASI MODEL MIMIC DALAM MENGIDENTIFIKASI BIAS JENDER DALAM PENGUKURAN MINAT BERWIRAUSAHA - Wahyu Widhiarso; Handoko Wijatmiko (UII, 2013)
This study aimed to demonstrate the use of MIMIC Model methods to identify items that tend to bias when measuring individual attributes. Individuals attribute, which were explored in this study was entrepreneurship interest, which was reviewed by sexes. Participants in this study were students ( N = 129) with the percentage of 54 percent of men and 64 percent of women. Measurement instruments used in this study was Entrepreneurship Interest Scale, which was composed four dimensions, namely self-development, progression, variation of activity and independence. Analysis showed that of 27 items in the entirely scale contain two items from progression dimensions tends to be biased measured when examined by sexes. The first item measure entrepreneurship interest related to challenging while the second item measure interest in competition. Both items were proven beneficial to men than women, although both sexes have the same level of entrepreneurship interest. The presence of items bias when measuring showed that such items are less relevant to the dimensions measured. Challenges and competition are the pillars of successful entrepreneurship; however, measurements of these two indicators are susceptible to measurement bias. Therefore, measurements on both indicators need to be done carefully in order to provide accurate information.Keywords : Mimic Model, Item Bias, Entrepreneurship interest